Peningkatan Kemampuan Deteksi Dini Depresi pada Ibu Hamil di Kota Surabaya: Improvement of The Early Detection Ability of Depression in Pregnant Women in Surabaya City - Yuly Sulistyorini; Mahmudah Mahmudah; Nunik Puspitasari (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
The problems of pregnant women are not only physical health problems but also mental health problems. Mothers who experience mental and emotional health disorders are usually unable to carry out their daily functions properly and experience impaired fetal growth and development, social problems, and mental safety. So far, the examination of pregnant women and antenatal care efforts have focused more on efforts to maintain the physical health status of pregnant women and have not touched on the emotional health aspects, especially depression. So efforts to detect early and even prevent depression during pregnancy are significant. Increased knowledge and early detection of depression can help pregnant women prevent depression and provide solutions for appropriate treatment. This community service activity formed a class of pregnant women in RW 9, 13, and 14 as many as 28 people in Ujung Village, Semampir District, Surabaya City. The material was given directly by using a back sheet and leaflets. Pre-tests and post-tests are carried out before and after giving the material. The results of this community service activity showed that there was an increase in the ability to detect depression in pregnant women after attending classes for pregnant women on three materials (p=0,006; p=0.000; p=0,000; α=0.05). The ability to detect depression will prevent depression because pregnant women know the symptoms of depression that are visible or felt. So that pregnant women can make follow-up efforts and appropriate treatment if depression is detected.